Evaluation of the stability of linezolid in aqueous solution and commonly used intravenous fluids - Taylor, Rachel; Sunderland, Bruce; Luna, Giuseppe; Czarniak, Petra (Dove Medical Press Ltd., 2017)
Purpose: The aim was to evaluate the stability of linezolid in commonly used intravenous fluids and in aqueous solution to determine the kinetics of degradation and shelf-life values at alkaline pH values. Methods: Forced degradation studies were performed on linezolid in solution to develop a validated high-performance liquid chromatography analysis. Sodium chloride 0.9%, sodium lactate, and glucose 5% and glucose 10% solution containing 2.0 mg/mL linezolid were stored at 25.0°C (±0.1°C) for 34 days. The effect of temperature on the stability of linezolid in 0.1 M sodium hydroxide solution was investigated to determine the activation energy. The degradation rates of linezolid at selected pH values at 70.0°C and the influence of ionic strength were also examined. Activation energy data were applied to determine the shelf-life values at selected pH values, and a pH rate profile was constructed over the pH range of 8.7–11.4. The stability of intravenous linezolid (Zyvox®) solution was evaluated by storing at 70.0°C for 72 hours. Results: Linezolid was found to maintain > 95.0% of its initial concentration after storage at 25.0°C for 34 days in sodium lactate, 0.9% in sodium chloride, and 5% and 10% in glucose solutions. Linezolid was degraded at alkaline pH values by first-order kinetics. Activation energy data showed that temperature, but not ionic strength, influenced the degradation rate significantly. An activation energy of 58.22 kJ/mol was determined for linezolid in 0.1 M sodium hydroxide solution. Linezolid was least stable at high pH values and at elevated temperatures. It was determined that linezolid has adequate stability for the preparation of intravenous fluids for clinical administration. Conclusion: Linezolid was found to have a shelf life of 34 days at 25°C when added to sodium lactate, 0.9% sodium chloride, and 5% and 10% glucose solutions. It was least stable at high pH values and at elevated temperatures.